ANALYSIS OF CONFIRMATORY FACTORS TO MEASURE PUBLIC TRUST IN THE POPULATION DOCUMENT SERVICE OF POPULATION DEPARTMENT OF JAMBI CITY - ., Effiyaldi; Murniarti, Erni (Advances in Social Sciences Research Journal, 2020)
This study aims to identify indicator variables that can measure organizational transparency variables, work discipline and service quality to public trust in administering residence documents of the Department of Population of Jambi City. The research used Confirmation Factor Analysis method. This study found that Chi-square, RMSEA, GFI, NFI, CFI, IFI, RMR models have moderate fit. This means that organizational transparency, work discipline and service quality affect public confidence in the demographic document service of Jambi residence. The results of this study can be used as a consideration and evaluation of demographic document services for the community for improvement and increased public confidence in the future.